REDUCTION OF INORGANIC FERTILIZER AND APPLICATION OF ORGANIC FERTILIZER IN RICE PLANT - I Ketut Sumantra; I Ketut Widnyana; Putu Pandawani (International Journal of Applied Science and Sustainable Development (IJASSD), 2021)
The massive use of inorganic fertilizers without adequate organic fertilizers will cause land and plant productivity to decline. This study aims to obtain a combination of organic and inorganic fertilizers and their effect on rice production. The study used a Randomized Block Design with three replications and four treatments, namely a) full inorganic package (200 urea + 200 kg Phonska), b) organic fertilizer + 75% inorganic fertilizer, c) organic fertilizer + 50% inorganic fertilizer, d) organic + 25% inorganic fertilizers. Organic fertilizers are given as essential fertilizers, while half of the inorganic fertilizers are given when the plants are planted and the rest when the tillers are active. The results showed that: 1) Applying a combination of organic and inorganic fertilizers increased the percentage of productive tillers, weight of 1000 grains and weight of dry grain harvested per hectare. 2) Application of organic fertilizer + 75% NPK can increase grain weight by 4% compared to using only NPK fertilizer. The results of the study recommend that fertilizing rice with a combination of organic fertilizer + 50% NPK needs to be considered for increasing paddy grain production and improving the quality of rice fields.